3 surface root QTLs - qSFR2, qSFR5 and qSFR - confer salt tolerance when iintrogressed in IR64 background - CGIAR Research Program on Rice (2020)
Yield trials were conducted using 21 lines with introgressions of 3 root QTLs for surface rooting in background of IR64. Under saline conditions (salinity of 4 dSm-1) Sahel 108 and Sahel 134 had yields <1 tonne/ha. Introgression lines had yields >2.5 tonnes/ha.